Determination of Income, Production, and Employment Under Pollution Control: An Input-Output Approach - Rhee, Jeong J.; Miranowski, John A. (The Review of Economics and Statistics, 1984)
Jeong J. Rhee, John A. Miranowski, Determination of Income, Production, and Employment Under Pollution Control: An Input-Output Approach, The Review of Economics and Statistics, Vol. 66, No. 1 (Feb., 1984), pp. 146-150